2022
DOI: 10.3390/cancers14194787
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Indolent Cutaneous B-Cell Lymphoma with Intralesional or Intravenous Rituximab

Abstract: Indolent cutaneous B-cell lymphomas (CBCL) are a rare disease for which the therapeutic recommendations are based on clinical reports. Recommendations for solitary lesions include surgery or irradiation. However, the high relapse rates may require less invasive repeatable therapy. This study seeks to retrospectively assess the efficacy of intralesional rituximab (ILR) for indolent CBCL when compared with intravenous rituximab (IVR). Patients treated for indolent CBCL with ILR or IVR at the Division of DermatoO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our results showed no significant difference in response to treatment, rituximab retreatment, time to retreatment, disease progression or recurrence when comparing intralesional and systemic rituximab in indolent subtypes. These results align with a recent study that directly compared the two forms of rituximab in indolent subtypes and found no significant difference in treatment outcomes, disease‐free interval or relapse rates 17 . Given these findings, intralesional rituximab should be considered in select patients with indolent PCBCL for which the sequelae of surgery and radiation is a concern.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results showed no significant difference in response to treatment, rituximab retreatment, time to retreatment, disease progression or recurrence when comparing intralesional and systemic rituximab in indolent subtypes. These results align with a recent study that directly compared the two forms of rituximab in indolent subtypes and found no significant difference in treatment outcomes, disease‐free interval or relapse rates 17 . Given these findings, intralesional rituximab should be considered in select patients with indolent PCBCL for which the sequelae of surgery and radiation is a concern.…”
Section: Discussionsupporting
confidence: 87%
“…These results align with a recent study that directly compared the two forms of rituximab in indolent subtypes and found no significant difference in treatment outcomes, disease-free interval or relapse rates. 17 Given these findings, intralesional rituximab should be considered in select patients with indolent PCBCL for which the sequelae of surgery and radiation is a concern.…”
Section: Discussionmentioning
confidence: 99%
“…49 Therefore, complete excision alone, deferring radiation until disease recurrence, is also reasonable. Intralesional [e.g., corticosteroids or rituximab [58][59][60] or topical therapies including corticosteroids, nitrogen mustard and bexarotene may also be considered. 61,62 While radiation therapy is generally recommended for patients with a solitary lesion, radiation therapy or observation (i.e., "watch and wait") are reasonable options for those patients with multiple lesions.…”
Section: Pcfclmentioning
confidence: 99%